PERANCANGAN APLIKASI PERSONAL ORGANIZER DENGAN FITUR JEJARING SOSIAL UNTUK PERANGKAT MOBILE BERBASIS SISTEM OPERASI ANDROID - Budi Wasito (Jurnal Informatika dan Bisnis, 2012)
The existence and role of modern mobile phones should not be extraordinary things. The benefits obtained from the use of mobile phones are also increasingly seen the emergence of groups, mobile phones known as Smartphones. Now Smartphone must be connected to the Internet, as well as Androidbased Smartphone operating system. This operating system applications is growing rapidly along with human lifestyles changed and many take advantage of media technologies to solve their problems. Social media networks is also one of them, as well as a number of other applications, such as application organizer that helps to regulate the activities of each day. The objective of this study is to develop applications to be able to organize the schedule each day, and can also communicate directly with other people. Collecting information and the user needs to be done with literature study and observation.Â  Designed system is described by the unified modeling language and entity relationship diagrams. The results of this study is the Android-based management application that has a personal organizer functions and social networking. Data storage for this application is on the server.